Ukuleles in the elementary music classroom: using technology for virtual instruction - Conway, Haley (Kansas State University, 2020)
The lessons demonstrated in this report are focused on using ukuleles in the music classroom using virtual instruction. Ukuleles are a growing tool that are being used in music rooms and that are popular instruments to give students an opportunity to grow in a variety of musical ways. These lessons incorporate a Kodály inspired approach using solfege, identifying the parts of the ukulele, playing a melody using the open strings, and then creating a composition with a variety of rhythms with the open strings on the ukulele. Over the course of the past three years to complete my Masters’ degree, some major developments I have made were expanding my knowledge and understanding of different methodologies used in the elementary music classroom and incorporating new technologies into my teaching instruction. When creating the ukulele lessons for this Graduate Report, I explored and used some technology tools that I have used in my classes over the summers. For example, during the Introduction to Graduate Studies class, we learned more about Garage Band and Soundtrap. These programs could be used for teachers to create background tracks to encourage student learning and practice and also allow for students to create musical compositions. For my lessons, I used it as a warm-up to reviewing the open strings of the ukulele. Another way that I incorporated technology was the use of Zoom. In our classes, Zoom was used a lot for class meetings. Upon further research into the program, I learned you could record and share on your screen. I used this resource then to virtually teach my lessons when we had no contact with students this spring. These resources have provided another way to connect and create with my students in my music classroom.
Keywords: Virtual instruction; Elementary music; Composition; Ukulele